Pengaruh Green Marketing Dan Brand Image Terhadap Minat Beli Serta Dampaknya Pada Keputusan Pembelian Air Minum Le Mineral Pada Mahasiswa Universitas Islam Malang - Yeritama, Risma; Mardani, Ronny Malavia; Sholehuddin, Sulton (UNIVERSITAS ISLAM MALANG, 2025)
Abstract This study aims to analyze the effect of Green Marketing and Brand Image on purchase intention and its impact on purchasing decisions for bottled Le Mineral drinking water at students of the Islamic University of Malang. The method used is quantitative by distributing questionnaires to 99 respondents. The population of this study were students of the Islamic University of Malang who had bought Le Mineral at least twice. The sampling technique used was purposive sampling, for data processing using SmartPLS 4 software. The results in the study showed that Green Marketing and Brand Image have a significant positive effect on purchase intention and purchasing decisions, purchase interest has a significant positive effect on purchasing decisions, and purchase interest can mediate the relationship between the two to purchasing decisions. Keywords: Green Marketing, Brand Image, Purchase Intention, Purchasing Decisions.